The association between the knowledge, perception, and practice of dietary supplement among Chinese adults - Tan, Din Son; Wang, Xijie; Zhao, Xuechen; Zhao, Ai (Frontiers in Nutrition, 2024)
Rapid growth has been found in the market of dietary supplements (DS) in China.However, studies about the knowledge level, intentions and behavior related to DS remained limited in Chinese population. The current study aimed to explore the knowledge level, perception and practice towards DS among Chinese adults with crosssectional design among 1714 participants aged between 18 and 65 years. A total of 54.1% of participants reported purchasing supplements in the past six months. Knowledge levels were assessed with a score from 1 to 10 based on correct answers to 10 binary questions about supplements. Only 29.1% of participants answered 7 or more questions correctly, while 7.9% answered 3 or fewer questions correctly. Participants with high and middle knowledge levels were more likely to seek medical advice when experiencing discomfort symptoms and were less likely to choose DS, with corresponding odd ratios (ORs) of 1.58 (95% CI: 1.16, 2.13) and 0.69 (95% CI: 0.52, 0.91) in high knowledge group, and ORs of 1.36 (95% CI: 1.03, 1.80) and 0.96 (95% CI: 0.72, 1.30) in middle knowledge group (Pfor trend =0.003 and 0.028, respectively). No significant differences were found in motivation of DS use between knowledge levels. Although higher knowledge levels were associated with less spending on DS (OR high=0.69; 95% CI: 0.49, 0.99; OR middle=0.88; 95% CI: 0.64, 1.20; Pfor trend =0.038), it did not guarantee better and more accurate awareness towards DS use. In conclusion, there is a growing demand for supplements among Chinese adults, but a significant gap between knowledge and behavior exists, affecting decision-making behaviors regarding DS.